Divide each term in <math><mstyle displaystyle="true"><mi>a</mi><mrow><mo>(</mo><mi>n</mi><mo>)</mo></mrow><mo>=</mo><msup><mrow><mo>(</mo><mo>-</mo><mn>1</mn><mo>)</mo></mrow><mrow><mi>n</mi><mo>+</mo><mn>1</mn></mrow></msup><msup><mrow><mi>e</mi></mrow><mrow><msup><mrow><mi>n</mi></mrow><mrow><mn>2</mn></mrow></msup></mrow></msup></mstyle></math> by <math><mstyle displaystyle="true"><mi>n</mi></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>a</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Do you know how to Solve for x a(n)=(-1)^(n+1)e^(n^2)? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.